Kinematic and dynamic analysis of walking dynamic balance stability in children with spastic cerebral palsy diplegia - Ma, Tingting; Zhang, Qi; Zhou, Tiantian; Zhao, Hongbo; He, Yan; Feng, Tianyang; Yue, Qing; Li, Xiaosong; Zhang, Yanqing (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study aims to compare biomechanical features during walking between children with spastic cerebral palsy (SCP) and typically developing children, providing evidence to improve walking ability and prevent falls in children with SCP.MethodsThe study included 28 children with SCP from the paediatric physiotherapy department of the China Rehabilitation Research Centre (March 2023 to September 2024) and 28 typically developing children from a Beijing primary school as controls. Participants wore tight-fitting clothing to ensure clear visibility of reflective markers. A Vicon 3D motion capture system and AMTI force plates were used to collect data on temporal-spatial parameters, dynamic balance and kinematic parameters during gait cycles. Measurements included walking speed; step frequency, width and length; single-foot support time; peak displacements of the centre of mass (COM) and the centre of pressure; and joint angles of the pelvis, hip, knee and ankle in multiple planes.ResultsChildren with SCP showed significantly lower values in walking speed, stride length, step length and single-foot support time than the controls (P < 0.05). Conversely, cadence, stride time and double support time were higher in children with SCP than in the controls. Children with SCP showed greater peak COM displacement in the coronal plane but lower in the sagittal plane than the controls (P < 0.05). Significant differences were found in the range of motion of left lower extremity joints across various phases of the gait cycle (P < 0.05).ConclusionChildren with SCP exhibit distinct gait patterns and dynamic balance challenges compared with their typically developing peers, underscoring the importance of personalised rehabilitation treatments to enhance their walking abilities and prevent falls.Clinical Trial NumberChiCTR2300071226.